2020
DOI: 10.3389/fendo.2020.00194
|View full text |Cite
|
Sign up to set email alerts
|

RFRP-3, the Mammalian Ortholog of GnIH, Is a Novel Modulator Involved in Food Intake and Glucose Homeostasis

Abstract: RF amide-related peptide 3 (RFRP-3) is a reproductive inhibitor and an endogenous orexigenic neuropeptide that may be involved in energy homeostasis. In this study, we evaluated the effect of acute or chronic RFRP-3 treatment (administered via intraperitoneal injection) on the food intake, meal microstructure and weight of rats, as well as the mechanism through which RFRP-3 is involved in glucose metabolism in the pancreas and glucose disposal tissues of rat in vivo. Our results showed that the intraperitoneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 41 publications
(52 reference statements)
6
23
0
Order By: Relevance
“…injection of GnIH/RFRP-3 increased food intake in chicks [ 34 , 35 ], mice [ 40 ], rats [ 25 , 28 ], sheep [ 40 ], and cynomolgus monkeys [ 40 ]. In addition, a recent study showed that chronic intraperitoneal injection of RFRP-3 to rats stimulated feeding behavior and regulated blood glucose homeostasis [ 36 ]. However, the chronic central effects of RFRP-3 have not been elucidated in any animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…injection of GnIH/RFRP-3 increased food intake in chicks [ 34 , 35 ], mice [ 40 ], rats [ 25 , 28 ], sheep [ 40 ], and cynomolgus monkeys [ 40 ]. In addition, a recent study showed that chronic intraperitoneal injection of RFRP-3 to rats stimulated feeding behavior and regulated blood glucose homeostasis [ 36 ]. However, the chronic central effects of RFRP-3 have not been elucidated in any animals.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that body mass may be independent of food intake and may be related to the decrease in energy expenditure. It has been recently reported that intraperitoneally injected RFRP-3 slightly increased body mass and serum lipid levels in rats [ 36 ]. Although the serum glucose level was increased by the infusion of RFRP-3 in this study, no change in the serum lipid and insulin levels was found ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has further been confirmed in rats, as well as chickens, with insufficient fat stores resulting in pubertal delay ( 136 , 149 , 150 ) and diet-induced obesity resulting in declined reproductive capacity ( 151 , 152 ). In a recent study, GnIH injections resulted in the elevation of serum total triglycerides and cholesterol ( 153 ), leading to increased uptake of triglycerides by the adipose tissue ( 142 ). Thus, it could be hypothesized that GnIH acts to control fat deposition in adipose tissue not only in immature animals but also in adults.…”
Section: Gnih and Its Receptor In The Brain Involvement In Multiple Neuroendocrine Systemsmentioning
confidence: 99%
“…Regarding glucose metabolism, little is known about possible effects of RFRP‐3. Intraperitoneal administration of RFRP‐3 has been shown to change circulating glucose concentrations, as well as insulin receptor and glucose transporter expression in testis and adipose tissue, 13,56 and a lack of the RFRP‐3 receptor in NPFF1R KO mice worsened the metabolic impact of a high‐fat diet on glucose homeostasis in male but not female mice 6 . RFRP‐3 neurones also project to the NPY‐ and POMC‐containing neurones in the ARC 57 ; thus, in view of the reported opposite effects on POMC neuronal activity, 42 the comparable effects on glucose metabolism may appear unexpected.…”
Section: Discussionmentioning
confidence: 99%